Engineering and Economic Perspective in The Production of Cu Nano - Yuliandini, Annisa; Nandiyanto, Asep Bayu Dani (Universitas Jember, 2020)
The purpose of this study is to analyze the production of copper nanoparticles (Cu NPs) on an industrial scale in an engineering perspective and economic evaluation perspective. Energy is needed because of various energy related applications. Evaluation of Cu nanoparticle production in an engineering perspective is carried out from the selection of processes that are adapted to industrial scale, calculation of mass balance, to the adjustment of commercially available equipment. Evaluation of production from an economic point of view is done by calculating economic parameters: Gross Profit Margin, Internal Return Rate, Payback Period, Cumulative Net Present Value, Profitability Index, and Break Even Point. Briefly from the production process, we use Copper acetate hydrate (CuAc2.2H2O) (as a source of Cu), Tween 80 (polyoxyethylene-(80)-sorbitan monooleate) and ethylene glycol (as a reducing agent). The engineering viewpoint shows this process is capable of producing Cu nanoparticles which can be used as conductive nanoionic. Economic evaluation determines the process is beneficial, discussing with positive values ​​all economic parameters. However, for some variations this process is not profitable, so economic evaluation is needed.